2007
DOI: 10.1038/ng2033
|View full text |Cite
|
Sign up to set email alerts
|

p38α suppresses normal and cancer cell proliferation by antagonizing the JNK–c-Jun pathway

Abstract: The mitogen-activated protein kinase (MAPK) p38alpha controls inflammatory responses and cell proliferation. Using mice carrying conditional Mapk14 (also known as p38alpha) alleles, we investigated its function in postnatal development and tumorigenesis. When we specifically deleted Mapk14 in the mouse embryo, fetuses developed to term but died shortly after birth, probably owing to lung dysfunction. Fetal hematopoietic cells and embryonic fibroblasts deficient in p38alpha showed increased proliferation result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
347
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 340 publications
(379 citation statements)
references
References 43 publications
30
347
0
2
Order By: Relevance
“…Another work also showed that JNK activities are dramatically increased in p38-deficient livers in LPS-induced hepatitis, although it remains unknown whether increased JNK activities contribute to apoptosis of hepatocytes (Heinrichsdorff et al, 2008). During inflammation-associated liver cancer development, increased activities of the JNK pathway were found to cause the accelerated proliferation rates of liver tumor cells lacking p38α (Hui et al, 2007a). Increased MKK7 phosphorylation was proposed to explain the hyperactivation of JNK in p38α-deficient cancer cells.…”
Section: Crosstalk Between Mapk Signaling In Inflammation and Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…Another work also showed that JNK activities are dramatically increased in p38-deficient livers in LPS-induced hepatitis, although it remains unknown whether increased JNK activities contribute to apoptosis of hepatocytes (Heinrichsdorff et al, 2008). During inflammation-associated liver cancer development, increased activities of the JNK pathway were found to cause the accelerated proliferation rates of liver tumor cells lacking p38α (Hui et al, 2007a). Increased MKK7 phosphorylation was proposed to explain the hyperactivation of JNK in p38α-deficient cancer cells.…”
Section: Crosstalk Between Mapk Signaling In Inflammation and Cancermentioning
confidence: 99%
“…p38α-deficient MEFs proliferate faster and exhibit delayed senescence compared to control cells, due to the increased G1/S and G2/ M transitions by upregulation of cyclin D1 and inactivation of p53 activity (Hui et al, 2007a;Sun et al, 2007). Moreover, p38α is shown to be an important regulator of differentiation of various cell types.…”
Section: P38smentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] Initial experiments using mouse models of cancer showed that p38MAPK suppresses lung and liver tumour formation in vivo. 7,8 However, enhanced p38 phosphorylation also correlates with poor prognosis in some patients with breast cancer and hepatocellular carcinoma. 9,10 Similarly, overexpression or activation of p38MAPK has been reported in lymphomas, thyroid neoplasms and human lung tumours.…”
mentioning
confidence: 99%